Answer:
Explanation:
Assuming ray NR is the middle one, the angles add up like this:
m∠MNR + m∠RNP = m∠MNP
Substituting the given relations, ...
-2(x -4) + (-(3x -2)) = -2 - (6x -2)
-2x +8 -3x +2 = -2 -6x +2 . . . . . eliminate parentheses
-5x +10 = -6x . . . . . . . . . . . . . . . collect terms
x +10 = 0 . . . . . . . . . . . . . . . . . . . add 6x
x = -10 . . . . . . . . . . . . . . . . . . . . . subtract 10
Then the angle of interest is ...
m∠RNP = -(3x -2) = -(3·(-10) -2) = -(-32)
m∠RNP = 32